'Good women do not inherit land' : politics of land and gender in India - Rao, Nitya (New Delhi : Social Science Press : Distributed by Orient Blackswan, 2008)
Study on the rights of Santal women in Dumka District of Jharkhand.
Includes statistical tables.
Includes bibliographical references (p. [328]-342) and index.
Keywords: Women's rights -- India -- Dumka (District); Right of property -- India -- Dumka (District); Land tenure -- India -- Dumka (District); Santal (South Asian people) -- India -- Dumka (District) -- Politics and government